BUDIDAYA LELE SEBAGAI UPAYA PEMBERDAYAAN EKONOMI LOKAL DESA MACAN PUTIH KECAMATAN KABAT - Ahmad Aziz Fanani (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this activity is to realize the development of village and the independence of villagers in order to reduce unemployment and poverty. Macan Putih Village is the most widespread area and has many irrigation channels. In addition, there is a potential of human resources that has a high spirit in the implementation of the dedication and independence of the village. In order to realize the objectives above, there is a catfish cultivation training program in this village.